Strategic Options for Improved Organizational Performance in the Nigerian Telecommunication Industry: Miles and Snow Approach.: Array - Akingbade, Waidi Adeniyi (Acta Universitatis Danubius. Œconomica, 2021)
The global telecommunications industry has witnessed tremendous challenges in the last two decades. Telecommunications companies in Nigeria have formulated policies that could enable them to cope with the global challenge. However, most of them have not really employed strategic options that could enable them to cope with the changing condition. The main objective of this study is to examine the effect of Miles and Snows strategies which is considered the major approach that could promote competitiveness in the industry to enable them manage and survive other present and future challenges. The study adopted survey research design and population composed of 7,567 top and middle level management staff of four major service providers MTN, Airtel, Globacom and 9Mobile with sample size of 380 determined scientifically through Yamane’s (1967) formula. Combinations of judgemental and stratified random sampling techniques were used to select participants for the study from the selected telecommunication companies. Out of the 380 content validated questionnaire subjected to Cronbach’s Alpha measure of reliability distributed, 369 were retrieved representing a response rate of 97.1%. The study reaffirmed the efficacy of Mile and Snow’s competitive strategy. It was recommended that Telecom Company should adopt prospector, analyzer, and defender strategies to improve their performances.